Indução de voláteis em cocos nucifera (Arecaceae) por Brassolis sophorae (Linnaeus, 1758) (Lepidoptera: Nymphalidae) e biologia de Winthemia analis (Macquart, 1846) (Diptera: Tachinidae) - Queiroz, Abel Felipe de Oliveira (2015)
Plants have evolved various strategies to defend themselves against herbivory. Under herbivore attack, they emit volatile organic compounds that indirectly defend the plant, by attracting herbivore s natural enemies or directly by repelling the herbivore. The coconut tree, Cocus nucifera, is grown in all regions of the country, being predominant in the northeast and hold socio-economic importance for the country. In this sense, the objective of this study was to characterize the emission of volatiles by C. nucifera induced upon herbivory of Brassolis sophorae caterpillars and to assess the behavioral response of Winthemia analis, larval parasitoid of B. sophorae, to B. sophorae induced volatiles. In addition, the biology of W. analis was studied. Were collected, using the aeration process, volatiles emitted by C. nucifera under the following treatments: 1 undamaged plants; 2 mechanically-damaged plants and 3 plants upon herbivory of Brassolis sophorae caterpillars. The collected volatiles were chemically analyzed by gas chromatography coupled to mass spectrometry (GC-MS). The behavioral response of the parasitoid to the induced compounds was tested in a Y-tube olfactometer, and the life cycle was determined from 79 larvae emerged from 28 B. sophorae pupae. The compounds nonanal, decanal and two ketones, geranyl acetone and 6-methyl-5-hepten-2-one, were identified in the samples containing volatiles emitted by C. nucifera 48h after the application of the three treatments. The homoterpene (E)-4-8-dimethyl-1,3,7-nonatriene (DMNT) was identified only in the samples containing volatiles emitted by C. nucifera upon herbivory of Brassolis sophorae caterpillars and mechanically-damaged plants. The DMNT contribution was higher in the sample emitted by plants upon herbivory of Brassolis sophorae caterpillars than in the samples emitted by mechanically-damaged plants. W. analis files were not attracted to the odors emitted by C. nucifera upon herbivory of Brassolis sophorae caterpillars. The emergence rate of adults was about 73%. Were possible to check sexual dimorphism in the adults wings using geometric morphometric (p<0.0001). The morphological analysis of the W. analis adults show one characteristic in the male abdomen.